2018
DOI: 10.1177/1526602818771383
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Results of First-Line Treatment Strategies in Patients With Critical Limb Ischemia (CRITISCH Registry)

Abstract: CRITISCH registry data revealed that all first-line treatment strategies selected and indicated by the treating physicians met the suggested OPGs. CKD was an important determinant of patient prognosis after treatment regardless of the revascularization method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 40 publications
1
24
4
Order By: Relevance
“…These conservatively treated patients reported a 1-year survival of 81% and AFS of 72%. 21 Santema et al reported 1-year survival (73%) and AFS (73%) in 22 conservatively treated patients in 144 patients with CLI. 20 The slightly better results of CRITISCH group and Santema et al compared to our study could probably be explained by the older patients included in our study (76 vs 83 years old) and heterogeneity of the included conservatively treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…These conservatively treated patients reported a 1-year survival of 81% and AFS of 72%. 21 Santema et al reported 1-year survival (73%) and AFS (73%) in 22 conservatively treated patients in 144 patients with CLI. 20 The slightly better results of CRITISCH group and Santema et al compared to our study could probably be explained by the older patients included in our study (76 vs 83 years old) and heterogeneity of the included conservatively treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, endovascular treatments for patients with peripheral artery disease (PAD) of the lower extremities have gained growing acceptance among all vascular specialties and have become the primary mode of revascularization in both claudicants and patients with chronic limb-threatening ischemia (CLTI). 1 , 2 The continuous development of endovascular technologies has offered a variety of different modalities and devices for the treatment of peripheral atherosclerosis. 3 11 In the femoropopliteal segment, the introduction of paclitaxel drug-coated balloons (DCBs) has led to a paradigm shift from primary scaffolding with permanent metallic implants to a “leave nothing behind” or “leave less behind” approach.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 In several cohorts of >300 patients treated by standard endovascular techniques, AFS rates of 74% to 76% and 52% to 55% at 12 and 36 months, respectively, were reported. [19][20][21][22] In the majority of cases, patients were treated using plain balloon angioplasty. In the current study, AFS rates of 83.9%, 71.0%, and 67.2% were achieved at 6, 12, and 24 months, respectively, in CLTI patients with no further possibility of conventional revascularization.…”
Section: Discussionmentioning
confidence: 99%